Who’s counting? Inventories & NDC Network Newsletter - Sanz Cobena, Alberto; Pickering, Andrea; Chirinda, Ngonidzashe; Eckard, Richard (Global Research Alliance, 2019)
This newsletter contains articles written by the Network coordinators, general Alliance updates, and training and research opportunities of interest. Contributions are welcome, so if you have any opportunities or information to distribute to the wider GRA and Inventories and NDC network, please contact one of the Network coordinators listed below.